2013
DOI: 10.1111/acem.12151
|View full text |Cite
|
Sign up to set email alerts
|

Dating Violence: Outcomes Following a Brief Motivational Interviewing Intervention Among At‐risk Adolescents in an Urban Emergency Department

Abstract: Objectives A recent study demonstrated the efficacy of the SafERteens intervention in reducing peer violence among adolescents presenting to the emergency department (ED). The objective of this study was to determine the efficacy of this ED-based brief intervention (BI) on dating violence 1 year following the ED visit among the subsample of adolescents in the original randomized controlled trial reporting past-year dating violence. Methods Patients (aged 14 to 18 years) at an ED were eligible for inclusion i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 47 publications
0
43
0
Order By: Relevance
“…For those men ready to accept a referral to BIPs, research has shown that brief motivational interviewing improved attendance and treatment compliance among men enrolled in BIPs. 63,64 Although brief motivational interviewing to address adolescent dating abuse has been explored in the emergency department setting, 65,66 to our knowledge, brief motivational interviewing to address perpetration of IPV in primary care settings has yet to be explored.…”
Section: Motivational Interviewingmentioning
confidence: 99%
“…For those men ready to accept a referral to BIPs, research has shown that brief motivational interviewing improved attendance and treatment compliance among men enrolled in BIPs. 63,64 Although brief motivational interviewing to address adolescent dating abuse has been explored in the emergency department setting, 65,66 to our knowledge, brief motivational interviewing to address perpetration of IPV in primary care settings has yet to be explored.…”
Section: Motivational Interviewingmentioning
confidence: 99%
“…[103][104][105][106] While these programs have shown promise in ED studies, 88, 103-111 they have not specifically focused on youth firearm injuries or firearm-specific outcomes. Single session screening and brief interventions incorporating motivational interviewing 112 and cognitive behavioral therapy have also shown efficacy at reducing violence and/or drug use among at-risk adolescents. 113 However, prior efficacy studies among youth at risk for violence have not led to concurrent work focused on how to prevent firearm injury among the similar populations.…”
Section: Suicide (Table 2)mentioning
confidence: 99%
“…The "AlcoholEdu" program covers aspects of drinking norms, the effects of alcohol, laws and policies, goal setting, harm reduction and dealing with alcoholrelated problems (Paschall et al, 2011a;Wyatt et al, 2013). The "SafERteens" study used techniques adapted from motivational interviewing with a non-confrontational and non-judgmental stance, emphasizing choice and self-efficacy (Cunningham et al, 2013). All the interventions were of short-duration, ranging between 30 min and 3 h. To our knowledge, only the SafERteens program contained components specifically targeting perpetration or victimization of IPV or sexual violence.…”
Section: Study Characteristics -Interventionsmentioning
confidence: 99%